A PENGATURAN PENURUNAN DARI HAK MILIK MENJADI HAK GUNA BANGUNAN BAGI PERSEROAN TERBATAS - Sihotang, Tabitha Christina; Satyawati, Ni Gusti Ayu Dyah (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 1 (2023), 2023)
Land is the center of human life which also functions as a place to live and a place of life. Besides getting a life, it is also a place to live. In agrarian law, land ownership can be in the form of property rights, cultivation rights, building rights, rental rights, and use rights. Limited Liability Company as a business entity has the right to have building rights. Limited Liability Companies engaged in housing must change the status of property rights to building use rights. The problems in this paper are the first, the procedure for reducing property rights to building use rights carried out by a Limited Liability Company. Second, the obstacle in decreasing the status of land rights from property rights to building rights by Limited Liability Companies. Third, how to overcome obstacles to the decline in the status of property rights to building use rights. This study uses a normative research method with a statutory approach, a conceptual approach, and an analytical approach, namely legal norms related to land rights by Limited Liability Companies. The procedure for reducing property rights to building use rights by a Limited Liability Company is carried out by submitting an application to the local land agency accompanied by the identities of the parties, certificates of property rights being requested for reduction, location permits and in-principle permits. Meanwhile, there are obstacles in reducing property rights to building use rights in the form of complex implementation and long time. To overcome these obstacles, the National Land Agency needs to improve bureaucratic efficiency and narrow or shorten the time for the reduction of their rights.